Comparative Investigation of Fullerene PC71BM and Non-fullerene ITIC-Th Acceptors Blended With P3HT or PBDB-T Donor Polymers for PV Applications - Otieno, Francis; Kotane, Lesias; Airo, Mildred; Erasmus, Rudolph M.; Billing, Caren; Wamwangi, Daniel; Billing, David G. (Frontiers in Energy Research, 2021)
Fundamentally, organic solar cells (OSCs) with a bulk-heterojunction active layer are made of at least two electronically dissimilar molecules, in which photoabsorption in one (donor) generates Frenkel excitons. The formation of free charge carriers emerge after exciton dissociation at the donor:acceptor interface. In the past decade, most of the progress in enhanced device performance has been steered by the rapid development of novel donor and acceptor materials and on device engineering. Among these donor materials, regioregular poly(3-hexylthiophene) (P3HT) produced better performance despite the mismatch of its absorption coefficient with the solar emission spectrum. Comparatively the donor PBDB-T exhibits an outstanding absorption coefficient with a deeper-lying highest occupied molecular orbital (HOMO) level. Previously most of the efficient acceptors were based on fullerene molecules characterized by limited photoabsorption and stability. In contrast, the recently developed non-fullerene OSCs have a tunable absorption spectrum and exhibit improved stability. In this work, we explore the fundamental sources of the differences in the device performance for different blend compositions made of fullerene derivative (PC71BM) and non-fullerene (ITIC-Th) when paired with the polymer donors P3HT and PBDB-T. The characteristic changes of the optical properties of these blends and their roles in device performance are also investigated. We also studied charge generation where PBDB-T:PC71BM showed the highest maximum exciton generation rate (Gmax) of 3.22 × 1028 s–1 while P3HT: ITIC-Th gave the lowest (0.96 × 1028 s–1). Also noted, PC71BM based counterparts gave better charge transfer capabilities as seen from the lower PL quenching and higher charge carrier dissociation plus collection probability P(E,T) derived from a plot of Jph/Jsat ratio under short-circuit conditions against the effective voltages.